A novel series of indazole-/indole-based glucagon receptor antagonists. Issue 19 (1st October 2015) - Lin, Songnian; Zhang, Fengqi; Jiang, Guoqiang; Qureshi, Sajjad A.; Yang, Xiaodong; Chicchi, Gary G.; Tota, Laurie; Bansal, Alka; Brady, Edward; Trujillo, Maria; Salituro, Gino; Miller, Corey; et al.
Graphical abstract: Abstract: A novel, potent series of glucagon receptor antagonists (GRAs) was discovered. These indazole- and indole-based compounds were designed on an earlier pyrazole-based GRA lead MK-0893. Structure–activity relationship (SAR) studies were focused on the C3 and C6 positions of the indazole core, as well as the benzylic position on the N -1 of indazole. Multiple potent GRAs were identified with excellent in vitro profiles and good pharmacokinetics in rat. Among them, GRA16d was found to be orally active in blunting glucagon induced glucose excursion in an acute glucagon challenge model in glucagon receptor humanized (hGCGR) mice at 1, 3 and 10 mg/kg (mpk), and significantly lowered acute glucose levels in hGCGR ob/ob mice at 3 mpk dose.